Flexible Work Practices: A Source of Career Premiums or Penalties? - Leslie, Lisa M.; Manchester, Colleen Flaherty; Park, Tae-Youn; Mehng, SI Ahn (Academy of Management Journal, 2012)
The present research builds theory regarding how use of flexible work practices (FWPs) affects employees' career success. We integrate theory on signaling and attributions and propose that managers interpret employees' use of FWPs as a signal of high or low organizational commitment, depending on whether managers make productivity or personal life attributions, respectively, for employees' FWP use. Managers' perceptions of employees' commitment, in turn, shape employees' career success. Field- and laboratory-based studies provide strong support for the hypothesis that FWP use results in career premiums when managers make productivity attributions and some support for the hypothesis that FWP use results in career penalties when managers make personal life attributions.